Efikasi Teknik Relaksasi Benson Pada Skor Nyeri Pasien Acute Myocardial Infarction (AMI) - Adiratna Sekar Siwi; Danang Tri Yudono; Septiana Mixvora Sebayang; Awal Tunis (Citra Delima Scientific journal of Citra Internasional Institute, 2023)
The blockage that occurs in the coronary arteries causes blood flow to the heart muscle to stop/obstruct. Acute Myocardial Infarction is life-threatening which is dangerous because of chest pain, collapse, and sudden death. The main symptom of acute myocardial infarction is chest pain that does not go away even after resting. other symptoms that may appear are cold sweats, nausea, vomiting, coughing, palpitations, and dizziness. Relaxation can take the form of deep breathing, guided imagery, dhikr, listening to music, and Benson relaxation. The application of Benson relaxation can be applied to AMI sufferers in reducing the anxiety they feel. This study uses the Pre and post-test approach without control, using a sample of 40 respondents. Sampling by accidental sampling. The statistical test results found a significant difference in the patient's pain score before and after the intervention was carried out (p-value: 0.00). Further research is needed to see the efficacy of this therapy in a larger sample size.